Airline CEOs: Who are they, and what background and skill set are most commonly chosen to run the world's largest airlines?. (September 2019) - Wilson, Russell; Lohmann, Gui
Abstract: Purpose: This paper aims to narrow the knowledge gap for airlines preparing for CEO succession by testing whether CEOs with a finance background are more prevalent as leaders of the largest airlines. This paper focused on three themes: functional background, succession planning, and insider versus outsider. Design/methodology/approach: The study combined primary and secondary data, including a unique compilation of CEO profiles from the world's largest 100 airlines. This information highlighted the choices that company boards had made in selecting their leaders. Data was collected through the use of semi-structured interviews and emailed responses with twelve interviewees, consisting of CEOs, non-executive directors (NEDs), and executives and global airline consultants, all with experience from the top 100 airlines. Findings: The results indicate that the larger the airline, the more likely it is to have a finance CEO (50% of the top 10 airlines). However, operations CEOs dominate the top 100 airlines, with 24%. Succession planning has strong support, with 72% of CEOs being insiders. NEDs prefer insiders, whereas other interviewees were more open to outsiders. Sixteen per cent of CEOs had no previous airline experience. In 2016, 24% of the top 100 airlines changed their CEO, suggesting that boards may have to give more consideration to outsiders. Originality/value: No previous empirical research has been found that discusses the functional backgrounds of airline CEOs or any research that compares the profiles of airline CEOs. This study offers useful and practical guidance for airlines and their boards to improve how they prepare for and select their next CEO. Highlights: Do CEOs with a finance background more prevalent as leaders of major airlines? We analyse the profiles of CEOs from the world's largest 100 airlines. Key themes are functional background, succession planning, and insider vs outsider. The larger the airline, the more likely it is to have a finance CEO. Operations CEOs dominate the top 100 airlines, with 24%.